2007
DOI: 10.1042/cs20070136
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy induced by aortic banding impairs relaxation of isolated coronary arteries

Abstract: LVH (left ventricular hypertrophy) is associated with impaired coronary vascular reserve. In the present study, we examined the effect of pressure-overload hypertrophy on vasorelaxant responses of guinea-pig isolated coronary small arteries and compared them with mesenteric small arteries. Pressure-overload was induced by banding the ascending aorta of guinea-pigs. Haemodynamics, and ventricular, atrial and lung weights were measured 168 days after banding. Isolated coronary and mesenteric small arteries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Previous studies have reported that aortic banding causes a number of neuroendocrine changes, including elevated levels of catecholamines, natriuretic peptides, ET-1, and tumor necrosis factor-a, and inconsistently, activation of the renin-angiotensin system. 21 Treatment of aortic-banded animals with the selective SUR2B/Kir6.1 channel opener natakalim restored endothelial function in pressure-overloaded animals.…”
Section: Endothelial Dysfunction In Myocardial Hypertrophymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported that aortic banding causes a number of neuroendocrine changes, including elevated levels of catecholamines, natriuretic peptides, ET-1, and tumor necrosis factor-a, and inconsistently, activation of the renin-angiotensin system. 21 Treatment of aortic-banded animals with the selective SUR2B/Kir6.1 channel opener natakalim restored endothelial function in pressure-overloaded animals.…”
Section: Endothelial Dysfunction In Myocardial Hypertrophymentioning
confidence: 98%
“…20 Some investigators reported that pressure overload-induced LVH causes impaired relaxation of small coronary arteries to endotheliumdependent relaxants and impairment of both the coronary blood flows as a consequence of endothelial dysfunction. 21 Selective impairment of the large coronary artery endothelial function occurred with morphological abnormalities of the endothelium after chronic coronary pressure overload. 19 The endothelium plays a key role in regulating vascular and organ functions through diverse signaling pathways.…”
Section: Endothelial Dysfunction In Myocardial Hypertrophymentioning
confidence: 99%
“…; McGoldrick et al . ). Heart‐to‐body weight ratio, the commonly used index of cardiac hypertrophy, indicates that significant hypertrophy (an increase of around 50%) has developed by this time (similar in extent to that found by Kingsbury et al .…”
Section: Discussionmentioning
confidence: 97%
“…One of the advantages of this model is that the contralateral side can be used as a normotensive control. Previous studies found disparate effects of hypertension induced by aortic banding on endothelium-dependent function in aorta or coronary arteries [13, 27], probably due to the differences in the vascular beds studied and the location of the band. In this study, our finding that transverse aortic banding impairs endothelium-dependent dilatation in right-sided (hypertensive) cerebral arterioles in WT mice, but not in Nox2-/y mice, suggests that superoxide derived from Nox2-containing NADPH oxidase may play an important role in altered endothelium-dependent function in cerebral arterioles during hypertension.…”
Section: Discussionmentioning
confidence: 99%